The growth of reform Judaism: American and European sources - Plauṭ, Zeʾev Mosheh (JPS anthologies of Jewish thought, 2015)
1. Call for an American Synod (I.M. Wise) -- 2. Cleveland: Invitation-Articles of Union-To Unite the Most Divergent (M. Lilienthal)-Conservative Evaluation (I. Leeser)-A Reformer Protests (D. Einhorn) -- 3. The Board of Delegates: An Editorial (Jewish Messenger) -- 4. Cincinnati Conference, 1871 -- 5. Union of American Hebrew Congregations: Three Reasons (M. Loth)-Objectives (From the Constitution) -- CHAPTER III : RABBINIC UNION IN AMERICA -- 1. Philadelphia: Call-Resolutions.